1975
DOI: 10.1530/acta.0.0780634
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Luteinizing Hormone Releasing Hormone by Rat Hypothalamic L-Cystine Arylamidase

Abstract: The rate of hydrolysis of several aminoacyl-4-nitroanilides by rat hypothalamic arylamidases was investigated. The activity of these enzymes which were mainly found in the 105 000 \m=x\ g supernatant fraction of homogenates of the hypothalamus and other parts of the brain was shown to depend upon the presence of metal ions and free thiol groups, and to be inhibited by puromycin. As previous investigations had shown that Cys\ x=r eq-\ NA is an appropriate substrate for measuring hormone effects on hypothalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Similarly, 48 /¿g LH-RH are degraded by an enzyme preparation of one single PIT under the same experimental conditions. This is, however, in agreement with the previous results of Kuhl and Taubert [1975a], who ob served that only 25 /<g of biologically active LH-RH remained after 1 h when 59 /rg LH-RH were incubated with the supernatant of Zi of a rat HYP. The high degrading capacity of HYP peptidases was previously observed by Marks and Stern [1974], and by Koch et al [1974], who showed that the supernatant of one rat HYP inactivated 1 /zg LH-RH within 5 min.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similarly, 48 /¿g LH-RH are degraded by an enzyme preparation of one single PIT under the same experimental conditions. This is, however, in agreement with the previous results of Kuhl and Taubert [1975a], who ob served that only 25 /<g of biologically active LH-RH remained after 1 h when 59 /rg LH-RH were incubated with the supernatant of Zi of a rat HYP. The high degrading capacity of HYP peptidases was previously observed by Marks and Stern [1974], and by Koch et al [1974], who showed that the supernatant of one rat HYP inactivated 1 /zg LH-RH within 5 min.…”
Section: Discussionsupporting
confidence: 93%
“…In view of the previous extensive use [ Kuhl and Taubert, 1975a;1975b;Kuhl el al., 1976;1977;1978] grading enzymes (arylamidases), the type of inhibition was investigated. The inhibitory ef fect of concentrations of 0-100 fiM Cys-NA on the degradation of LH-RH (5,10 or 20 /jM) by HYP and PIT enzyme preparation during 30 min of incubation is shown in figure 3.…”
Section: Substrates Lh-rh (Pglu-mentioning
confidence: 99%
See 2 more Smart Citations
“…Individual hypothalami were homogenized in 2 ml phosphate-buffered saline and then heated for 5 min in a boiling water bath to inactivate endogenous peptidases known to degrade LH-RH (Griffiths, Hooper & Hopkinson, 1973;Kuhl & Taubert, 1975;Gradwell, Millar & Symington, 1976). After centrifugation and appropriate dilution of the supernatant, LH-RH content was determined by radioimmunoassay with a specific antiserum raised to LH-RH conjugated to keyholelimpet haemocyanin and 125I-labelled LH-RH (Hendricks, Millar & Pimstone, 1975).…”
mentioning
confidence: 99%